"Entrelaçando as linhas do crochê com as vidas de jovens em processo de reinserção social: colocando em valor o patrimônio cultural imaterial através de medidas socioeducativas" - Alves, Isabel Angélica Scoto (2025)
This project investigates the value of crochet craft activities carried out at the Socio-Educational Assistance Center of Santa Maria (CASE-SM) as a tool for the social reintegration of adolescents under socio-educational measures. The research seeks to understand how this practice contributes to the personal and professional development of young people, while also valuing and preserving the intangible cultural heritage associated with crochet. The main objectives are to analyze the learning process and commercialization of crochet crafts at CASESM, to investigate the contribution of crochet to the social reintegration of adolescents, and to highlight its transmission to future generations. The methodology combines qualitative and quantitative approaches, including field research with observation, interviews, and dialogues with adolescents and staff, as well as bibliographic and documentary analysis on the subject. The expected results include a deeper understanding of the role of crochet in social reintegration, the promotion of intangible cultural heritage, and the development of public policies that support the reintegration of adolescents under socio-educational measures.